Modeling the oxidation process of TiAl and Ti3Al intermetallic compounds due to grain-boundary diffusion of oxygen - M. V. Chepak-Gizbrekht; A. G. Knyazeva (Учёные записки Казанского университета: Серия Физико-математические науки)
A diffusion-kinetic model was proposed to analyze the oxidation process in a nanostructured material with explicit identification of grain boundaries. It was assumed that oxygen migrates faster along the boundaries than it does in the grain volume. The model takes into account the stages of decomposition and formation of intermetallic compounds, as well as the formation of oxides, both within the boundaries and in the grain volume. The problem was solved numerically, and the oxidation dynamics were compared for various materials with different grain properties.